The role of small-scale sports events in developing sustainable sport tourism – a case study of fencing - Vargáné Csobán , Katalin; Serra , György (Applied Studies in Agribusiness and Commerce, 2014)
Promoting sports and sport tourism is considered as a strategic development objective at the local, regional and national levels in Hungary. However, sport tourism is present in many different forms, depending on the type of sport activity, the related sport events and its participants, therefore it is challenging to decide on the type of sports and sports events that should be supported to ensure long-term social and economic benefits for a local community. The scale of sports events ranges from the small, local competitions to the international mega sports events. Although the economic benefits of mega sports events are generally appreciated, there has been growing critique about their negative social and environmental impacts. Smallscale sports events also have important potential for tourism, and they may have more advantages for the local community than the mega events by providing additional incomes, using the already existing infrastructure, raising local pride and community spirit. Sport tourism related to small-scale events is generally considered to be a more sustainable form of tourism. The purpose of this paper is to examine the tourism development potential of small-scale sports events, particularly focusing on fencing competitions. It highlights the demand side of the sport tourism market, investigating the behavioral profile of the participants of an international fencing tournament. A questionnaire survey was conducted at the Budapest WestEnd Women’s Epee Grand Prix 2014. The data revealed that participants of the sporting event spend only a short period of time at the destination, and shopping and eating out are the most preferred free time activities. The paper identifies and discusses issues regarding the role of sports organizations and tourism agencies in cities hosting such events to increase the tourism potential of small-scale sports events in the future.